Colorblind and multicultural diversity strategies create identity management pressure - Kirby, T. A. (2021)
Colorblind and multicultural diversity strategies may create identity management pressure, leading minorities to assert or distance from their racial identity. In two experiments (N = 307, 279), Asian and Asian American participants in the United States completed racial identification measures, contemplated employment at a company expressing a multicultural, colorblind, or control strategy, and completed measures assessing ingroup similarity and comfort in the company. In the colorblind condition, participants who were strongly identified with their racial ingroup downplayed similarity to the ingroup and expressed less comfort relative to multicultural and control conditions. Participants who were weakly identified reported more similarity (but inconsistently) and more comfort in the colorblind relative to multicultural and control conditions. Thus, diversity strategies convey different meanings to strongly and weakly identified Asian individuals, with the former responding to colorblindness with identity distancing and the latter with identity assertion. Multiculturalism does not alter the typical pattern expected, with strongly identified asserting their identity more than weakly identified.